Socialization Of Excise Sector Provisions Through Activities With IHT Central Java (International Journal of Scientific Research and Management (IJSRM), 2023)
Research aims: This research is to find out the extent of outreach, the benefits of outreach to the community, provide solutions for the development of legal IHT IKMs as well as suppress legal IHT products, increase the competitiveness of IHT products in the market, explore the potential of IHT in the regions, and get support from various interested parties in IHT development Design/Methodology/Approach: This research is a descriptive research. It begins with the research/survey conducted. The research was conducted in Kudus Regency. Research takes 1 month. The type of data used is mainly data obtained from the results of questionnaires distributed to individual participants in child socialization and to individuals who do not participate in socialization. The entire population in this study were participants in the socialization of cigarette excise provisions carried out by the Central Java Industry Office, Kudus Regency. This survey uses a sample of at least 30 socialization participants and an additional 30 people who do not take part in socialization but are still prioritized are socialization participants. Data analysis techniques were carried out using quantitative and qualitative methods Research findings: The results showed that based on the results of observations and the results of the questionnaires, it was found that cigarettes with counterfeit excise bands were found to be the highest in Kudus Regency. And, from the socialization participants agreed that cigarettes need to be attached with excise tape Theoretical contribution/Originality: The novelty of this research is through community groups to continue or continue socialization activities so that there are stricter regulations and increased sanctions against illegal tobacco producers, distributors and consumers. Practitioner/Policy implication: Both the government and especially the Kudus area where there are many cigarettes without excise stamps to be repaired and adjusted immediately Keywords: Socialization; Excise Ribbon; IHT; and Cigarettes